Krisis Kapitalisme 2008 dan Bangkitnya Gerakan Kiri Studi Dinamika Gerakan Partai Syriza di Yunani - Arif Novianto; Lukman Kurniawan; Samodra Wibawa (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2016)
The economic crisis which hit Greece was in 2008 helped to flow into a political crisis. The old political oligarchy that since 1974 up to 2010 alternately dominate the Greece that is PASOK party and the New Democracy party suffered shocks that lead to new political dynamics. Austerity policies and neoliberal reforms under the moderation of the troika (Europaen Central Bank, European Union, and International Monetary Fund) have created a decrease in the level of welfare and the economic crisis are instead growing. That situation creates a distrust of the Greek people, until they are searching for an alternative system other than capitalism. At that time the idea of socialism promoted by Syriza party has been able to to gain influence in the mass base, to deliver Syriza-led government with 36.3 percent of voters in Election 2015. This paper attempts to elaborate on the strategies used by the Syriza party and also weaknesses in the startegy